Collaborative Learning through Social Media in Arabic Language Teaching - Salem Al-Yusufy; Fatma Azzahra (IJAS: International Journal of Arabic Studies, 2026)
This study aims to investigate the role of collaborative learning through social media in Arabic language teaching and its contribution to enhancing learner interaction, language skills, and learning engagement in the digital era. The study employed a qualitative approach using a library research design by reviewing books, journal articles, and previous studies related to collaborative learning, social media, and Arabic language education. Data were collected from various academic sources and analyzed through content analysis and thematic analysis. The findings reveal that social media platforms provide interactive learning environments that promote communication, cooperation, and knowledge sharing among learners. Furthermore, collaborative learning through social media enhances learner motivation, autonomy, digital literacy, and communicative competence. The study also identifies several challenges, including limited digital literacy, technological constraints, and the need for institutional support. Therefore, the study recommends integrating social media into Arabic language instruction to create more engaging, collaborative, and student-centered learning environments in contemporary education.